The Role of Universities in Society Service in Extraordinary Unstable Conditions: Libya as Case Study - Aragib, Fatima Abdu Asalam (The Arab Journal of Administration, 2024)
In spite of the bulk number of studies that investigated the role of universities in society service and its surrounding environment during normal conditions, its role during unstable and unexpected conditions has not been widely tackled by researchers. Research significance and objectives: The objective of this study is to analyze the role of the university in community and society service in unstable changing environment. Though the study is focusing on the role of the universities in Libya during and after the 17th of February uprising, it adopts a comparative approach to examine the role played by western, and regional universities in similar circumstances. The research problem: The main problem of this study is to answer the following key question: “What is the role of Libyan universities in serving the society during the current exceptional and unstable conditions? What is the suggested strategy to activate this role?” Research methodology: The study will use the following approaches: Case study approach. Comparative approach. System analysis approach. Results: Through this comparative analysis on the international, regional and national levels the study came to the following results: While these is a great similarity in the role played by western and regional universities, in society service during stable ordinary situation Libyan universities ware paging behind. During extraordinary unstable conditions the situation of the universities in Libya was even worse. Internal conflicts dominated the scene and overcame the role that the universities should play in community services. No attempt was made by the Libyan universities to bring about peace and coexistence. Found out the absence of clear plans followed by Libyan universities particularly in unstable conditions, therefore a strategy was proposed.